PENINGKATAN KEMAMPUAN MEMAHAMI BACAAN DAN KEMANDIRIAN DENGAN TEKNIK RENCANA PRABACA - Zuchdi, Darmiyati (LITERA, 2015)
<img src="data:image/png;base64,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